Brand characters` influence on perceived brand personality - Peterská, Nikol (2022)
The appeals of a favourable brand personality have made brand personality a core focus of branding strategies. The usage of anthropomorphism to affect brand personality is also on the rise globally. This thesis therefore concerned itself with uncovering the relationship between brand characters and perceived brand personality with secondary objectives including assessing the mediating influence of humour and nostalgia on their relationship. The focus of the research were differences between how human and animal-type brand characters used in commercials are perceived. Four brands prominent in Czech TV using different types of brand characters were therefore reviewed. The research was designed in form of semi-structured interviews using guideline questions based on the research of Aaker (1997) and Cohen (2014). The research had two phases which together resulted in twenty-nine interviews being held. The dimensions of brand characters with most impact on perceived brand personality were found to be Behavior, Affect and Interpersonal relations. The brand personality traits most influenced by the characters were sincerity and competence. The usage of humour by brand characters further enhanced perceived brand sincerity and competence. The findings highlight importance of relatability and cultural belonging of brand characters. Marketers are advised to at first consider the usage of animal-type brand characters for the benefits suggested by the findings.